Low dose compared to variable dose Warfarin and to Fondaparinux as prophylaxis for thromboembolism after elective hip or knee replacement surgery; a randomized, prospective study. Issue 1 (December 2015) - Bern, Murray; Hazel, Diane; Deeran, Elizabeth; Richmond, John; Ward, Daniel; Spitz, Damon; Mattingly, David; Bono, James; Berezin, Ronna; Hou, Laura; Miley, Gerald; Bierbaum, Benjamin
Abstract Background Deep vein thrombosis (DVT) and pulmonary emboli (PE), known together as venous thromboembolic (VTE) disease remain major complications following elective hip and knee surgery. This study compares three chemoprophylactic regimens for VTE following elective primary unilateral hip or knee replacement, one of which was designed to minimize risk of post-operative bleeding. Methods Patients were randomized and stratified for hip vs. knee to receive A: variable dose warfarin (first dose on the night preceding surgery with subsequent target INR 2.0–2.5), B: 2.5 mg fondaparinux daily starting 6–18 h postoperatively, or C: fixed 1.0 mg dose warfarin daily starting 7 days preoperatively. All treatments continued until bilateral leg venous ultrasound day 28 ± 2 or earlier upon a VTE event. The study examined primary endpoints including leg DVT, PE or death due to VTE and secondary endpoints including effects on D-dimer, estimated blood loss (EBL) at surgery and hemorrhagic complications. Results Three hundred fifty-five patients were randomized. None was lost to follow-up. Taking 1.0 mg warfarin for seven days preoperatively did not prolong the prothrombin time (PT). Two patients in Arm C had asymptomatic distal DVT. One major bleed occurred in Arm B and one in Arm C (ischemic colitis). Elevated d-dimer did not predict delayed VTE for one year. Conclusions Fixed low dose warfarin started preoperatively is equivalent to two other standards of care under study (95 % CI: -0.0428, 0.0067 for both) as VTE prophylaxis for the patients having elective major joint replacement surgery. Trial registration ClinicalTrials.gov identifier #NCT00767559 FDA IND: 103, 716